Placebo Response Rates in Randomized Controlled Trials for Perianal Crohn's Disease: A Systematic Review and Meta-Analysis. (22nd October 2022) - Sharma, Tanmay; Ma, Christopher; Sedano, Rocio; Hanzel, Jurij; McDonald, Cassandra; Hogan, Malcolm; Kochhar, Gursimran S; Narula, Neeraj; Peyrin-Biroulet, Laurent; Danese, Silvio; MacDonald, John K; Jairath, Vipul
Abstract: Background and Aims: Perianal fistulizing disease is a common complication of Crohn's disease [CD], for which new therapies are urgently needed. To assist the design of clinical trials for novel therapeutics, we conducted a systematic review and meta-analysis of randomised controlled trials [RCTs] to quantify placebo rates and identify factors influencing them in perianal CD [pCD]. Methods: We searched MEDLINE, Embase and CENTRAL from inception to June 2021. Eligible studies were placebo-controlled trials of pharmacological interventions for pCD. Placebo fistula response and remission rates for induction and maintenance trials were extracted and pooled using a random-effects model. Mixed-effects meta-regression was used to evaluate the impact of patient and study-level characteristics on point estimates. Results: In 17 RCTs [13 induction, five maintenance] the pooled placebo fistula response and remission rate for induction trials was 25% (95% confidence interval [CI] 17–36%) and 17% [95% CI 11–25%], respectively. For maintenance trials, the pooled placebo fistula response and remission rate was 23% [95% CI 17–32%] and 19% [95% CI 14–25%], respectively. Trials enrolling patients with less disease activity and a higher proportion with ileal predominant disease were associated with significantly higher placebo response rates. Trials originating in Europe [compared to North America], therapies requiring perianal injection and a longer timepoint to measure remission were associated with higher placebo remission rates. Conclusions: Placebo response and remission rates in pCD trials are influenced by patient and disease-related factors, as well as the type of intervention being studied. These contemporary rates will inform trial design for novel therapeutics.